2008
DOI: 10.1007/s10719-008-9189-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of human and murine isoforms of UDP-N-acetylglucosamine 2-epimerase/N-acetylmannosamine kinase (GNE)

Abstract: The bifunctional enzyme UDP-N-acetylglucosamine 2-epimerase/N-acetylmannosamine kinase (GNE) is the key enzyme for the biosynthesis of sialic acids, terminal components of glycoconjugates associated with a variety of physiological and pathological processes. Different protein isoforms of human and mouse GNE, deriving from splice variants, were predicted recently: GNE1 represents the GNE protein described in several studies before, GNE2 and GNE3 are proteins with extended and deleted N-termini, respectively. hG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 30 publications
(4 reference statements)
1
31
0
Order By: Relevance
“…hGNE3 (NM_001190388) is extended and deleted compared to hGNE1; it has 717 amino acids with its start codon in exon 1 at nucleotide −191 (Figure 1). Note that the start codons in exon 1 for hGNE2 and hGNE3 are at different positions (21, 22). Bioinformatic database searches revealed two additional hGNE transcript variants, encoding hGNE4 (NM_001190383) and hGNE5 (NM_001190384), skipping the in-frame exons 10 and 5, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hGNE3 (NM_001190388) is extended and deleted compared to hGNE1; it has 717 amino acids with its start codon in exon 1 at nucleotide −191 (Figure 1). Note that the start codons in exon 1 for hGNE2 and hGNE3 are at different positions (21, 22). Bioinformatic database searches revealed two additional hGNE transcript variants, encoding hGNE4 (NM_001190383) and hGNE5 (NM_001190384), skipping the in-frame exons 10 and 5, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, two different mouse Gne mRNA splice variants were described, Gne1 and Gne2 , together with their expression in selected tissues (22). In the current study we identified additional human isoforms hGNE4-8, and demonstrate expression of hGNE isoform transcripts in a wide variety of tissues.…”
mentioning
confidence: 99%
“…Interestingly, GNE3 seems to be restricted to primates, whereas GNE1 and GNE2 appear ubiquitous among vertebrates. However, the partial deletion of the epimerase domain in GNE3 leads to the total loss of the respective enzymatic activity, whereas the kinase domain is still intact [40]. Together with the fact that the GNE3 protein has been analyzed as a recombinant protein only, the question arises whether GNE3 exists as a protein in vivo at all.…”
Section: The Gne Proteinmentioning
confidence: 99%
“…However, the existence of each isoform in vivo has not been demonstrated yet on the protein level. Recombinant over-expression of the human isoforms revealed that GNE1, which is the original described 722 amino acids containing isoform, has the highest epimerase activity, whereas the two other isoforms with 31 additional N-terminal amino acids (GNE2) or a different N-terminus (GNE3) displayed strongly reduced epimerase activity [40]. Since the C-terminus of GNE is known to harbor the kinase domain, it was not surprising that ManNAc kinase activity was similar in all isoforms.…”
Section: Regulation Of Gnementioning
confidence: 99%
See 1 more Smart Citation